2015
DOI: 10.1177/0308518x15619934
|View full text |Cite
|
Sign up to set email alerts
|

Value creation and value capture in the automotive industry: Empirical evidence from Czechia

Abstract: This article investigates how distinct tiers of firms contribute to value creation and value capture in the automotive industry. We employ firm-level indicators to evaluate the value creation and capture of distinct supplier tiers in the Czech automotive industry, while considering differences between foreign-owned and domestic firms. Our analysis suggests that the economic effects of the automotive industry largely depend on its capital intensity and that mostly foreign-owned higher tier firms generate and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 79 publications
1
49
0
4
Order By: Relevance
“…Firstly, disadvantaged suppliers are rarely able to achieve functional upgrading in GVCs (Dolan & Humphrey, ; Humphrey, ; Schmitz & Knorringa, ). Secondly, the occurrence of functional or other upgrading does not necessarily enhance disadvantaged suppliers' ability to capture higher profits (Pavlínek & Ženka, ; Plank & Staritz, ; Smith, Pickles, Buček, Pástor, & Begg, ). Furthermore, there seem to be distinctive strategies that suppliers can adopt to improve their profit margins in GVCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, disadvantaged suppliers are rarely able to achieve functional upgrading in GVCs (Dolan & Humphrey, ; Humphrey, ; Schmitz & Knorringa, ). Secondly, the occurrence of functional or other upgrading does not necessarily enhance disadvantaged suppliers' ability to capture higher profits (Pavlínek & Ženka, ; Plank & Staritz, ; Smith, Pickles, Buček, Pástor, & Begg, ). Furthermore, there seem to be distinctive strategies that suppliers can adopt to improve their profit margins in GVCs.…”
Section: Resultsmentioning
confidence: 99%
“…This paper set out to review the empirical literature related to the implications of upgrading for developing country suppliers, with special focus on disadvantaged suppliers, in terms of their profit margins (Murphy & Schindler, ; Plank & Staritz, ). Based on the analysis of 44 empirical studies, we have concluded that under certain conditions, disadvantaged suppliers are able to capture more gains in GVCs by other means than functional upgrading or in addition to it (Pavlínek & Ženka, ; Pickles et al, ). Disadvantaged suppliers tend to operate under challenging conditions in terms of their institutional environment and high degree of competitive pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2014). According to Pavlínek and Ženka (2016), foreign-owned companies create and capture more value than the lower tier domestic companies in Central Europe. Actual gains from GVCs in Central Europe therefore need to be empirically examined.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the experiences of Mexico and Central American countries as assembly manufacturers have been likened to the creation of an enclave economy, with few domestic linkages (Gallagher and Zarsky, 2007;Dussel Peters, 2008). The same can be said about the electronics and automotive industries in Eastern and Central Europe (Plank and Staritz, 2013;Pavlinek, 2015;Pavlinek and Zenka, 2016). There has been significant "internal upgrading" within MNE affiliates, but it has involved very few spillovers to the domestic economy in the form of productivity improvements and imitation by domestic firms, partly due to limited linkages of MNEs with local firms and labour markets (Fons-Rosen et al, 2013;Paus, 2014).…”
Section: E Global Value Chains Industrial Upgrading and Structural mentioning
confidence: 99%